Unveiling Uncommon Etiologies of Acute Generalized Exanthematous Pustulosis - A Case Series - Thomas, Irene Nirmala; Sadiq, Sahana Begum Mohamed; Shanmugam, Nithya Priyadharshini; Bala, Arishta; Mohan, Saranya (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Acute Generalized Exanthematous Pustulosis (AGEP) is a rare, severe adverse cutaneous drug reaction characterized by fever and numerous sterile, non-follicular pustules on an erythematous base that manifests 2 to 14 days after drug exposure. While systemic antibiotics, particularly beta-lactams and macrolides, are frequently implicated, they can also be triggered by other drugs, including hydroxychloroquine, antifungals, antivirals, antineoplastics, and herbal remedies like Ginkgo biloba, curcumin, etc. This case series reports three unusual instances of AGEP after intake of tablet paracetamol, native medicines, and syrup azithromycin. All three patients met the EUROSCAR diagnostic criteria for AGEP, with scores indicating a definite diagnosis. Treatment included the withdrawal of the offending drug, symptomatic management, topical and systemic steroids, resulting in the resolution of lesions within a week. This series emphasizes the necessity of considering rare and less common etiologies, highlighting that drugs like paracetamol, native medicines, and azithromycin, while infrequently associated, can still provoke AGEP. Comprehensive evaluation of all possible triggers is crucial for accurate diagnosis and effective treatment.